1963
DOI: 10.1038/icb.1963.52
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vasopressin on Water and Electrolyte Excretion by the Sheep

Abstract: SUMMARY The acute effects of vasopressin (40 mU) were studied in the conscious sheep. Vasopressin caused consistent increases in K and C1 excretion and variable increases in Na and total solute output. These changes occurred within 10 min., reached a peak within 30 min. and subsided within 60 min. When the urine was initially dilute (< 800 μosmoles/ml.) vasopressin caused an antidiuresis. When the original concentration exceeded 1000 (μosmoles/ml. vasopressin caused small increases in urine flow. Vasopressin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1968
1968
1980
1980

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 1 publication
2
17
0
Order By: Relevance
“…In other studies Cross, Thornton and Tweddell [1963] and Cross and Thornton [1966] found that the diuretic response to vasopressin in sheep occurred only if the osmotic concentration of the urine were initially high and SchmidtNielsen [1964] argued that in these circumstances the increase in urine flow is a consequence of the increase in electrolyte excretion due to the vasopressin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies Cross, Thornton and Tweddell [1963] and Cross and Thornton [1966] found that the diuretic response to vasopressin in sheep occurred only if the osmotic concentration of the urine were initially high and SchmidtNielsen [1964] argued that in these circumstances the increase in urine flow is a consequence of the increase in electrolyte excretion due to the vasopressin.…”
mentioning
confidence: 99%
“…In other studies Cross, Thornton and Tweddell [1963] and Cross and Thornton [1966] found that the diuretic response to vasopressin in sheep occurred only if the osmotic concentration of the urine were initially high and SchmidtNielsen [1964] argued that in these circumstances the increase in urine flow is a consequence of the increase in electrolyte excretion due to the vasopressin. Against these observations Brook, Radford and Stacy [1968] have produced evidence suggesting that vasopressin has no special role in regulating electrolyte excretion in the sheep and they suggest that the effects seen by these other workers were possibly the result of infusing unphysiologically large amounts of the hormone.…”
mentioning
confidence: 99%
“…Vasopressin administration into sheep usually causes increased potassium excretion and less reliably, increased sodium excretion also [Kinne, Macfarlane and Budtz-Olsen, 1961;Cross, Thornton and Twedell, 1963;Kuhn and Peeters, 1965]. Administration of cholinergic compounds into the carotid artery or into the third ventricle of hydrated animals causes falls in urine flow and increased urinary concentration which have been interpreted as resulting from increased release of vasopressin [Abrahams and Pickford, 1956;Olsson, 1970;Vandeputte-Van Messom and Peeters, 1973;Kuhn, 1974].…”
Section: Discussionmentioning
confidence: 99%
“…A similar response to vasopressin has been observed in the rat (Sawyer, 1952;Chan, 1965) although in one report (Heller & Stephenson, 1950) increased excretion of potassium was associated with reduced sodium excretion. In contrast vasopressin administration to sheep undergoing water diuresis usually causes increased potassium excretion with the effects on sodium excretion being the more variable (Kinne, Macfarlane & Budtz-Olsen, 1961;Cross, Thornton & Twedell, 1963;Kuhn & Peeters, 1965). The renal electrolyte response has proved to be even less reliable when vasopressin was given to animals in anti-diuresis.…”
Section: Introductionmentioning
confidence: 99%